Membangun Remaja Produktif dengan Pergaulan Positif: Jauhi Narkoba dan HIV - Endah Sari Purbaningsih; Dewi Erna Marisa; Ani Nurhaeni; Rosalia Rahayu; Lili Wahyuni R; Thia Oktiany; Muadi Muadi (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Free association among adolescents is often interpreted as social interaction that is no longer controlled by religious, social, and cultural norms. It can take the form of free sex, alcohol use, smoking, and drug abuse. This not only has an impact on the physical and psychological aspects of adolescents, but also increases the risk of sexually transmitted diseases such as HIV/AIDS. Juvenile delinquency often occurs due to association, unhealthy friendships, lack of attention from the family supporting the occurrence of this delinquency. There are many forms of juvenile delinquency, such as drug abuse, free sex behavior. To prevent juvenile delinquency, it is necessary to provide knowledge about this theme. Knowledge can be obtained formally or informally. Informal knowledge can be provided through several methods such as counseling. This activity has succeeded in equipping adolescents with the knowledge, skills, and motivation to stay away from drugs and HIV. An approach that involves active participation and creativity has proven effective in building productive adolescent character. Continued collaboration between schools, families, and communities is needed to support the sustainability of the program.